Hubungan Antara Gaya Kepemimpinan dengan Manajemen Konflik pada Karyawan RSI PKU Muhammadiyah Pekajangan Pekalongan - Sulthon, Muhammad Rofiansa (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2024)
A leader has a very important role, namely in managing the company or management to move the wheels of operations. A good leader can mobilize his employees, a good leader can also resolve conflicts that exist between his employees. So, to test this, a test was carried out to find out the relationship between leadership style and conflict management at RSI PKU Muhammadiyah Pekajangan. Testing was carried out by distributing questionnaires to employees within RSI PKU Muhammadiyah Pekajangan. The data that has been obtained is analyzed using a correlation test to determine the relationship between leadership style and conflict management. The results obtained show that at RSI PKU Muhammadiyah Pekajangan, it does not show that these two things are related, so that in reducing conflict at RSI PKU Muhammadiyah Pekajangan, a particular leadership style is not needed.